The Concept of Parenting Patterns in Broken Homes from an Islamic Psychological Perspective - Sugeng Sejati; Meliani Meliani; Nur Iliyin; Alia Rahmah (Yayasan Darussalam Bengkulu, 2026)
Divorce and broken home family structures are often associated with negative developmental outcomes in children. However, emerging scholarship suggests that children’s adjustment is influenced more significantly by post-divorce parenting quality than by family structural intactness alone. This study aims to analyze parenting patterns in broken home families through the perspective of Islamic Psychology and to synthesize them with modern developmental psychology frameworks. Using an integrative literature review methodology, this research critically examines empirical and conceptual studies on divorce, parenting styles, child adjustment, and Islamic educational thought. The findings identify three primary vulnerabilities in broken home parenting contexts: (1) inconsistency in parenting practices, (2) weakened emotional attachment, and (3) discontinuity in value transmission. Nevertheless, adaptive child development remains attainable when parenting is structured, emotionally responsive, and value-consistent. While modern developmental psychology highlights the effectiveness of authoritative parenting characterized by balanced control and warmth, Islamic Psychology expands this framework by emphasizing the concepts of fitrah, moral habituation, spiritual responsibility, and continuity of parental amanah. This study proposes an integrative value-based parenting framework consisting of four core principles: continuity of parental responsibility, balance between structure and affection, consistency of moral transmission, and reinforcement of spiritual development. Theoretically, this research contributes by bridging developmental psychology and Islamic educational thought, offering a holistic parenting paradigm applicable to broken home family contexts.